Analysis and System Design Optimization of PV Panel and Auxiliary Battery Integration for VIPV Electric Vehicles - Yavasoglu, Huseyin; Shani, Benjamin; Hasnain, Arafat; Parlak, Berke; Khaligh, Alireza (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2025)
Vehicle integrated photovoltaics (VIPV) is an emerging technology requiring multidimensional analysis to support its standardization and adoption in electric vehicles (EVs). This study examines the integration of photovoltaic (PV) systems into EVs, focusing on dc-dc converter topologies transferring solar energy to the vehicle's low-voltage (LV) electrical system across various auxiliary battery voltage levels. Three converter topologies, dual-active bridge (DAB), LLC, and flyback converters, are evaluated in terms of efficiency, cost, and volume. System performance is assessed under defined daily driving scenarios and auxiliary load profiles in two U.S. regions, Maryland and Arizona, which differ significantly in solar irradiance. A case study shows VIPV systems can supply up to 60.5% of annual secondary electrical load demands. The findings highlight that the choice of converter topology has a substantial impact on overall system efficiency and energy savings. Additionally, the study explores the environmental implications of large-scale VIPV adoption in the U.S. and globally, illustrating its potential to reduce the carbon footprint of EVs and advance sustainable transportation.
Keywords: Batteries; Topology; Zero voltage switching; Voltage control; Photovoltaic systems; Electric vehicles; Maximum power point trackers; Costs; Transportation; Buck converters; DC-DC converter optimization; photovoltaic (PV)-assisted electric vehicles (EVs); solar energy; CONVERTERS; OUTPUT; Engineering